Reassembling Economic Sociology: Methodological Traces of Actor-Network Theory - Potapova, Vera (Journal of Economic Sociology, 2024)
Actor-network theory (ANT), originating as a methodology within Science and Technology Studies (STS), has provided a new theoretical impetus to other fields of social sciences in the 21st century. It has significantly influenced contemporary economic sociology, as well as urban studies, sociology of art and culture. In the first part of the article, the author traces the genesis of the ideas of actor-network theory developed by the French sociologist Bruno Latour as described in his book ‘Reassembling the Social: An Introduction to Actor-Network Theory’. In contrast to conventional critical sociology which adjusts social interactions under overarching theory, the sociology of associations closely examines actors’ autonomous contributions to organising human and non-human assemblages. Following the structure of the book, the author describes the uncertainties faced by the sociologist and the subsequent steps to overcome them which altogether form the methodological approach of actor-network theory. The second part of the article provides an overview of contemporary works in the field of economic sociology that incorporate the theoretical insights of ANT’s. It includes Michel Callon’s perspective on the performative effect of economics as well as his heuristic concept of ‘market devices’. Consequently, the article discusses ANT’s impact on the research of markets material conditions developed by economic sociologists Donald MacKenzie, Fabian Muniesa and others within the emerging domains of Social Studies of Finance and Sociology of Valuation.